2013
DOI: 10.1371/journal.pone.0067663
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Gene Expression and Function in a South African Population: Ethnicity, Vitamin D and FokI

Abstract: Polymorphisms of the vitamin D receptor gene (VDR) have been associated inconsistently with various diseases, across populations of diverse origin. The T(f) allele of the functional SNP FokI, in exon 2 of VDR, results in a longer vitamin D receptor protein (VDR) isoform, proposed to be less active. Genetic association of VDR with disease is likely confounded by ethnicity and environmental factors such as plasma 25(OH)D3 status. We hypothesized that VDR expression, VDR level and transactivation of target genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 52 publications
0
38
0
2
Order By: Relevance
“…One potential exception is the FokI variant that has a differential effect on the immune system. 51,52 Our results indicated that the ApaI polymorphism a functional effect on MS. Additionally, the TaqI polymorphism was implicated in MS risk. However, its expression was influenced by environmental factors such as age and publication year.…”
Section: Discussionmentioning
confidence: 50%
“…One potential exception is the FokI variant that has a differential effect on the immune system. 51,52 Our results indicated that the ApaI polymorphism a functional effect on MS. Additionally, the TaqI polymorphism was implicated in MS risk. However, its expression was influenced by environmental factors such as age and publication year.…”
Section: Discussionmentioning
confidence: 50%
“…Of the eleven papers identified, seven were relevant experimental reports investigating VDR polymorphisms in South African populations (Table 4). Five related to disease [38,86,87,89,90], and two to ethnicity alone [85,88]. The first study on VDR single nucleotide polymorphisms (SNPs) in South African Whites, Blacks and Asian-Indians showed a significantly higher frequency of Taq I “TT” and ApaI “AA” genotypes in Blacks compared to Whites and Asian-Indians [85].…”
Section: Vitamin D Receptor Gene (Vdr) Polymorphisms and Ethnicitymentioning
confidence: 99%
“…A recent study of Black African and Coloured adults in Cape Town found Fok I “AG” associated with lower serum 25(OH)D levels, as well as a lower 25(OH)D status in winter and following supplementation with vitamin D [38]. The impact of Fok I on VDR function was examined using monocytes from healthy South African Blacks and Whites [90]. Despite having higher levels of more active VDR, monocytes from Blacks showed reduced transactivation of the gene encoding the cathelicidin antimicrobial protein (CAMP), compared to Whites, unless supplemented in vitro with 1,25(OH) 2 D 3 .…”
Section: Vitamin D Receptor Gene (Vdr) Polymorphisms and Ethnicitymentioning
confidence: 99%
“…Placental tissue obtained with PTB exhibited reduced mRNA expression of VDR gene compared to normal placental tissue [29]. Allele F in VDR produce shorter protein by three amino-acids which are more active form in transactivation of the VDR and producing 1, 25 (OH) D effect compared to f allele of VDR gene [30]. Results of the present study indicated that subjects with ff genotype have significantly more risk to develop PTB compared with the reference genotype FF.…”
Section: Patel Et Almentioning
confidence: 69%